TINJAUAN HUKUM ISLAM TERHADAP METODE BIBIT BEBET BOBOT DALAM MEMILIH PASANGAN SUAMI ISTRI DI DESA PLUMBON KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Khoiruddin, Dzikri; Syamsuddin, S; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Marriage is a sacred worship for muslims, in its implementation have rules that have been described in Al-Qur’an and Hadits. To achieve a harmonious marriage and not against islamic law, then there is a need for good marriage knowledge. One of the science of marriage is to choose a good partner, among them by choosing lineage, rank, beauty, partner’s religion. Islam regulates marriage not only for the satisfaction of sex relations, but aim to make a family that is sakinah, mawaddah, warahmah. In creating a harmonious and ideal family, javanese people have a bibit bebet bobot method in order to choose his life partner. In this research the author uses Qualitative Research. By using Descriptive Qualitative method by explaining the conditions in the field with data obtained through interviews, observation and documentation. Data analysis using data reduction method, data presentation and conclutions from research result. The result of the author’s research indicate that (1)The bibit bebet bobot method already existed in the days of Kartasura kingdom. Bibit means the origin of the partner, bebet comes from the word “bebetan” in javanese means clothing (economic and social caste), bobot means self-quality (education). (2)Islamic law reviews that the bibit bebet bobot method is in accordance with islamic sharia, as in islamic law there is kafa’ah. (3)The bibit bebet bobot method in modern times is still considered relevant but with the development of new languages or terms but with the same purpose.